Impact of green human resource management on sustainable performance in government city council department in peninsular Malaysia - Pavitra, Chandran; Sangeetha, Vengadeshwaran; Wong, Keng Yam; Yong, Jia Chee (2019)
Green human resource management is the use of HRM policies such a way to promote sustainable use of resources in business organizations to make eco-friendly and promote environmental economical sustainability practices to keep healthier environment by increasing employee awareness and commitments on the issues of sustainability. The purpose of this research is to help organization and the HR managers in Government City Council in Peninsular Malaysia to adhere the importance of practicing Green HRM and to understand how the practice able to impact on their employee’s performance. By conducting this research, it allows HR manager to gain more insight regarding the GHRM practice among the Government City Council employees by identifying each issues. This investigation is to analyze how each variable able to influence the employee’s performance in term of green management culture, green training and development, green recruitment and selection, green reward systems, green employee empowerment and participation, and green performance management and appraisal. From this research, it allows to see the correlation of each issue in impactions employee performance. A quantitative data analysis was executed with where the target population were focus on the employees working in Government City Council in Peninsular Malaysia. However, the exact amount of the target population for government city council is unknown, stratified random sampling was used. There were 106 samples was collected from the target population and it is good enough to test the research model because the G.Power software calculated 103 sample size meanwhile based on Bougie & Sekaran (2016) the sample size was 311. Smart PLS version 3.2.6 was used to test 7 hypotheses. Throughout this study, we have found that green employee empowerment and participation and green training and development affected the sustainable performance in Government City Council in Peninsular Malaysia. Manger implication, future research study and the limitations of the study was discussed in detail